Local correlation of delta-DOR signals with low signal-to-noise ratio and severe radio frequency interference. (7th July 2021) - Ma, Maoli; Li, Peijia; Tong, Fengxian; Zheng, Weimin; Kondo, Tetsuro; Rui, Ping; Chu, Zhanghu; Liu, Lei; Wu, Xiaojing; Zheng, Xin
Abstract: The Chinese very long baseline interferometry net (CVN) has applied the delta differential one-way ranging (delta-DOR) radiometric tracking technique to determine the orbit of a lunar and a deep-space spacecraft. In the past observations, CVN had sometimes encountered a difficult observation situation that the DOR signals were extremely weak or severely interfered. The CVN FX correlator, usually cannot process these extremely weak DOR signals. In order to enhance the weak signal processing capability of CVN, here we report an alternative method called 'local correlation'. By this method, the distinct DOR signals structure features of the narrow bandwidth sinusoidal tone and their coherent phase, are used to extract the exact frequency and phase of each tone. We have adopted the method on the weak signal case, then compared with the results obtained from CVN FX correlator. Analysis result shows the local correlation method can process DOR tone at lower signal-to-noise ratios such as 1 dBHz. The method also has advantages of high anti-interference, low computation cost and high efficiency. Furthermore, the delta-DOR delay obtained from local correlation can improve the orbit accuracy and reduce the arc length required by the orbit determination after the trajectory course maneuver.